Russian Turkestan and the First World War - Morrison, A (Slavica Publishers, 2024)
The First World War had a profound impact even on regions of the Russian Empire that were very distant from the front. This was particularly true of its most colonial periphery, the Governor-Generalship of Turkestan, which saw the first major rebellion against the Tsarist regime in the summer of 1916. This article explores the direct links between Turkestan and the front, the conscription of soldiers and labourers from the region and its hosting of tens of thousands of Austro-Hungarian prisoners of war. It examines the economic impact of the war, the course of the 1916 revolt, and the role of wartime legacies in the revolutionary and civil war years that followed.